Natural Killer Cells and Regulatory T Cells Cross Talk in Hepatocellular Carcinoma: Exploring Therapeutic Options for the Next Decade - Bozward, Amber G.; Warricker, Frazer; Oo, Ye H.; Khakoo, Salim I. (Frontiers in Immunology, 2021)
Despite major advances in immunotherapy, hepatocellular carcinoma (HCC) remains a challenging target. Natural Killer (NK) cells are crucial components of the anti-HCC immune response, which can be manipulated for immunotherapeutic benefit as primary targets, modulators of the tumour microenvironment and in synchronising with tumour antigen specific effector CD8 cells for tumour clearance. Regulatory T cells shape the anti-tumour response from effector T cells via multiple suppressive mechanisms. Future research should therefore focus on the development of novel NK cells-targeted immunotherapy and on restraining Treg frequency and function in HCC. We have now entered a new era of anti-cancer treatment using checkpoint inhibitor (CPI)-based strategies. Combining GMP-NK cell immunotherapy to enhance the frequency of NK cells with CPI targeting both NK and CD8 T cells to release co-inhibitory receptors and enhance the cells anti-tumour immunity of HCC would be an attractive therapeutic option in the treatment of HCC. These therapeutic approaches should now be complemented by the application of genomic, proteomic and metabolomic approaches to understanding the microenvironment of HCC, which together with deep immune profiling of peripheral blood and HCC tissue before and during the treatment will provide the much-needed personalised medicine approach required to improve clinical outcomes for patients with HCC.